Involvement of Husband in Antenatal Care in a Tertiary Level Hospital, Kathmandu - Parajuli, Puspa; Paudel, Narayani (Journal of Karnali Academy of Health Sciences, 2020)
Background: A husband at the antenatal clinic is rare in many communities and it is unthinkable to find men accompanying their partners during antenatal care and delivery. Male involvement in antenatal care is promoted to be an important intervention to increase positive maternal and new born health outcomes. So the objective of this study was to find the involvement of husband in antenatal care in a tertiary level hospital. Methods: A descriptive, cross-sectional study was conducted in the antenatal ward of Kathmandu Medical College Teaching Hospital. Data collection was done from December 1, 2019 to January 30, 2020. A total of 280 antenatal mothers were purposively selected for the study. Results: Majority of the respondents (67.1%) were between the age group of 20 to 29years with the mean ± S.D = 27. 70 ± 4.85 years, and their husbands (51.4%) were also between the age group of 20 to 29years with the mean ± S.D = 29. 63 ± 5.14years. The majority (74.6) of the respondents’ husbands encouraged their wives to take nutritious food during pregnancy and helped in domestic chores (76.4%). Most (74.6%) of the husbands encouraged their wives to attain antenatal clinics and two third (66.4%) had companied their wives for antenatal visit. More than half of the husbands (54.6%) had a high involvement during the antenatal period. there was a statically significant association between the level of husband involvement and age, ethnicity, education and occupation of the husbands’ P value < 0.05). Conclusion: Majority of the husbands had a high involvement during pregnancy but the number of husbands who accompanied their wives during the antenatal checkup is quite low. The level of husband involvement during pregnancy was associated with age, ethnicity, education and occupation of the husbands